THE EFFECTIVENESS OF USING TEAM GAMES TOURNAMENT IN STUDENTS UNDERSTANDING ON PAST TENSE AT SECONDGRADE OF MTS ROUDHOTUL KHUFFADZ 2016/2017 - Sudibyo, Doni; Nursalim, Nursalim; Sa’adah, Sitti Nur (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
This study aimed at knowing wether Team Games Tournament (TGT) is effective in students’ understanding on past tense or not. This study had conducted at Mts Roudhotul Khuffadz in second grade that focused on two classes VIIIa (as the control group) and VIIIB (as the experimental group) . The sample were fourthy students. The data were collected by using pre test and post test test. The form of the test was essay. After giving the pre-test, then the researcher giving the treatment and the steps in teaching learning proses were ;(1.) the teacher gave the explanation ;(2) the teacher devides the students become four groups ;(3) each group discuss the sheetwork that has given by the teacher ;(4) each group presentation their worksheet to be the winner ;(5) if the students in each group cannot answer the question or giving the wrong answer, it will be open the opportunity to the others group to answer. After giving the treatment, the researcher gave post test. The researcher was using Quantitative research and quasi experimental as the design. The data were analyzed by using T-test Formula. The result of the study indicate that Team Games Tournament (TGT) was effective to the students in understanding past tense. It shown from the result data, it showed that the result of post-test in experimental class(a class which is using Team Games Tournament “TGT” ) is higher than control class( a class which is given conventional method ). It can be seen from the mean score where 74,5 is higher than 70,55. The effectiveness of Team Games Tournament (TGT) is also proved from the result of T-test in which is 2,407 2.021. When was higher than , (Alternative Hypothesis) was accepted. The researcher conclude that Team Games Tournament (TGT) was effective in students understanding past tense.